Clinical Oral Anatomy : A Comprehensive Review for Dental Practitioners and Researchers - von Arx, Thomas; Lozanoff, Scott (Springer International Publishing : Imprint: Springer, 2017)
This superbly illustrated book presents the most current and comprehensive review of oral anatomy for clinicians and researchers alike. In 26 chapters, the reader is taken on a unique anatomical journey, starting with the oral fissure, continuing via the maxilla and mandible to the tongue and floor of the mouth, and concluding with the temporomandibular joint and masticatory muscles. Each chapter offers a detailed description of the relevant anatomical structures and their spatial relationships, provides quantitative morphological assessments, and explains the relevance of the region for clinical dentistry. All dental health care professionals require a sound knowledge of anatomy for the purposes of diagnostics, treatment planning, and therapeutic intervention. A full understanding of the relationship between anatomy and clinical practice is the ultimate objective, and this book will enable the reader to achieve such understanding as the basis for provision of the best possible treatment for each individual patient as well as recognition and comprehension of unexpected clinical findings.
Keywords: Dentistry.; Human anatomy.; Oral surgery.; Maxillofacial surgery.; elektronické knihy; electronic books